Carbon Monoxide in Healthcare Monitoring Balancing Potential and Challenges in Public Health - Dr Prodipta Barman,; Dr Joydeb Patra, (The Bioscan, 2025)
Carbon monoxide (CO), a colorless and odorless gas, poses significant risks to public health due to its toxic effects when inhaled at elevated levels. Advances in healthcare monitoring have enabled the detection and management of CO exposure, aiding in early diagnosis and prevention of poisoning. This abstract examines the dual role of CO as both a health hazard and a potential biomarker for certain physiological processes, such as cellular signaling and inflammation. We discuss the challenges of integrating CO monitoring technologies in public health systems, including affordability, accessibility, and data accuracy, while also exploring the opportunities for leveraging these tools in early intervention strategies. A balanced approach is required to harness the benefits of CO monitoring while mitigating its inherent challenges, ensuring its effective application in public health frameworks.